Peritoneal dialysis throughout pregnancy with successful outcome: A case report. (June 2018) - Malin, GL; Wallace, SVF; Hall, M; Ferraro, A
We present the case of a 28-year-old woman who was para 1, with end-stage renal failure secondary to reflux nephritis. She conceived after two years on peritoneal dialysis. She successfully continued this throughout pregnancy, although her antenatal course was complicated by an episode of peritonitis. Induction at 34 weeks resulted in a vaginal birth of a live boy. Her postnatal course was uncomplicated. We reviewed the literature regarding peritoneal dialysis in pregnancy. A recent systematic review identified 14 cases. When the outcomes of these women were compared with those receiving haemodialysis in pregnancy, there was a significantly higher proportion of small for gestational age fetuses, but other parameters were comparable. Two cases of peritonitis complicating peritoneal dialysis in pregnancy have been reported, both successfully treated. We conclude that peritoneal dialysis may be continued in pregnancy with successful maternal and fetal outcome, particularly in women with some residual renal function.